Flux ramp modulation based MHz frequency-division dc-SQUID multiplexer - Richter, Daniel Philipp; Hoibl, Ludwig; Wolber, Thomas; Karcher, Nick; Fleischmann, Andreas; Enss, Christian; Weber, Marc; Sander, Oliver; Kempf, Sebastian (Applied physics letters, 2021)
We present a MHz frequency-division direct-current superconducting quantum interference device (dc-SQUID) multiplexer that is based on flux ramp modulation and a series array of N identical current-sensing dc-SQUIDs with tightly coupled input coil. By running a periodic, sawtooth-shaped current signal through additional modulation coils being tightly but non-uniformly coupled to the individual SQUIDs, the voltage drop across the array changes according to the sum of the flux-to-voltage characteristics of the individual SQUIDs within each cycle of the modulation signal. In this mode of operation, an input signal injected in the input coil of one of the SQUIDs and being quasi-static within a time frame adds a constant flux offset and leads to a phase shift of the associated SQUID characteristics. The latter is proportional to the input signal and can be inferred by channelizing and down-converting the sampled array output voltage. Using a prototype multiplexer as well as custom readout electronics, we demonstrate the simultaneous readout of four signal sources with MHz bandwidth per channel.